Circular Economy in Morocco: Status and Perspectives and Policy Implications for Vietnam - Van, Truong Hoang Thuy (Darul Yasin Al Sys, 2024)
This paper explores the current status of the circular economy (CE) in Morocco, its potential future directions, and policy implications for Vietnam. The concept of CE, which promotes sustainable resource use, waste reduction, and regeneration, is increasingly gaining global traction. Morocco, having made significant progress in sectors such as waste management, agriculture, renewable energy, and water resource management, serves as a valuable case study. Key initiatives like the National Solid Waste Management Program (PNDM) and the